Pemahaman Mengenai Pengelolaan Manajemen Keuangan Masjid Al-Ikhlas Blok VI Griya Martubung - Ridho, Ridho Gilang Adiko; Aisyah, Siti; Sari, Purwita; Wardhani, Irine Ika; Siregar, Ratih Anggraini; Insani, Nurul Dwi (Publikasi Pengabdian Masyarakat, 2022)
The purpose of the Abdimas activity with the title "Understanding of the Financial Management of Masjid Al-Ikhlas Blok VI Griya Martubung" is to provide new insights for mosque managers regarding mosque financial management to be better both in terms of management or use of the money as well as reporting. . In addition, this abdimas is also expected to be able to help mosque managers to be able to compile mosque financial reports so that financial management runs optimally and transparently. The benefits obtained from this activity are expected to add insight to the managers of the Al-Ikhlas mosque on how to manage and manage the mosque's finances well. v Alternative problem solving is carried out by direct training on the management of mosque operational activities during the construction of the Al-Ikhlas mosque. With direct training to mosque managers, they can immediately apply the knowledge gained when the abdimas material is explained, and from that it can also be seen and measured whether the goal of this abdimas is achieved or not. In the process of building the Al-Ikhlas Mosque which is still ongoing, of course, good financial management must be applied to mosque administrators or mosque BKM. This is because the funds currently in the mosque treasury are joint funds which are a form of infaq and alms for the residents who live in Block VI Griya Martbung and there is also a grant from the Medan City Government. So what is the money used for, it must be reported clearly and correctly and the mosque administrator must be able to manage the use of the finance properly according to the needs of the mosque construction so that it can be completed quickly. At first the abdimas participants who were mosque managers did not understand how to properly manage or manage finances for the mosque construction process. However, after this abdimas was implemented, some of the problems that arose in the formulation of the problem could be resolved, namely the mosque managers became more proficient in managing the mosque's finances for the operational activities of mosque construction.Keywords: Understanding, Management, Mosque Financial Management